(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
This paper presents a mathematical model for detecting a single-phase to ground fault by using the frequency characteristics. The variety of types of single-phase-to-ground faults on overhead power lines significantly complicates the development of one universal method for its recognition and determination of the alleged place of damage. An additional aggravating factor is the complex configuration of district electrical networks, where up to several dozen consumers can be on one feeder, and the total length of its overhead line reaches several tens of kilometers. The most dangerous demonstration of single-phase to-ground fault is the resulting overvoltage’s in the network. The intermittent arc at the site of the single-phase-to-ground faults serves as a source of higher harmonics, which, in turn, due to "resonant" phenomena, can reach unacceptable values. It follows that for the correct reproduction on mathematical models of emerging phenomena, it is necessary to use the mathematical theory of long lines. Higher harmonics caused by single-phase-to-ground faults can serve not only as an indicator of the occurrence of damage, which is already being implemented in existing microprocessor relay protection terminals, but also provide information on the approximate location of the site with single-phase-to-ground fault. The mathematical model is initiated from a simplified equation for long distance transmission. To asses the accuracy of the calculation performed for the power transmission in equation its model was made in the Simulink Package and the overhead line was introduced into the model as an object with distributed parameters. Increasing the level of short-circuit currents on the buses of the power center leads to the upsetting the resonant peak of the frequency response signal relative to the beginning of the line, which makes it preferable to use frequency characteristics relative to the end of the transmission. In this case, combinations of network parameters and the magnitude of the contact resistance are possible, when the "resonant" amplification of higher harmonics is not evident